Management of strategy concepts and cases - Hitt, Michael A.; Ireland, R. Duane; Hoskisson, Robert E. (South-Western, a part of cencage learning, 2011)
This text explains how firms achieve strategic competitiveness, emphasising integration of resources and capabilities to obtain a sustained competitive advantage. The text integrates the resource-based view of the firm with the more traditional model